Distribution records of Helina Robineau-Desvoidy, 1830 (Diptera: Muscidae) from the Caucasus Mountains, with the descriptions of three new species - Pont, Adrian C. (Zootaxa, 2012)
Previous literature on the genus Helina Robineau-Desvoidy, 1830 in the Caucasus Mountains is reviewed, and records aregiven for 17 species from Armenia and Georgia, of which nine are new records for Armenia and eight are new records forGeorgia. In addition, three new species are described: Helina edita sp. nov. (Georgia, Turkey, Russia), Helina karina sp. nov. (Armenia) and Helina marisha sp. nov. (Armenia).